Prevention of Labour-Associated Pelvic Floor Injuries – What is Known for Sure - Franz, H. B.G.; Erxleben, C.; Franz, A.; Hofmann, R. (Geburtshilfe und Frauenheilkunde, 2012)
In order to avoid pelvic floor injuries a caesarean section is on the one hand often requested by the pregnant women and, on the other hand, offered by obstetric staff. For both forms of delivery, comprehensive risk-benefit analyses should be carried out before deciding in favour of the surgical procedure. The present brief review summarizes the current evidence on the avoidance of pelvic floor injuries.
Keywords: pelvic floor injuries; delivery method; incontinence; genital prolapse